2016
DOI: 10.1038/srep24489
|View full text |Cite
|
Sign up to set email alerts
|

A MALDI-MS-based quantitative analytical method for endogenous estrone in human breast cancer cells

Abstract: The level of endogenous estrone, one of the three major naturally occurring estrogens, has a significant correlation with the incidence of post-menopausal breast cancer. However, it is challenging to quantitatively monitor it owing to its low abundance. Here, we develop a robust and highly sensitive mass-assisted laser desorption/ionization mass spectrometry (MALDI-MS)-based quantitative platform to identify the absolute quantities of endogenous estrones in a variety of clinical specimens. The one-step modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The differentiation is based on variance between groups by rejection of the null hypothesis or acceptation the alternate hypothesis [101,107,108]. The most common methods used when the data is parametric are T-tests [31,47,48,50,53,57,59,62,68,70,71,73,74,76,77,78,79,84] and ANOVA [33,44,46,63,64,66,68,69,72,83] T-tests, such as Student and Welch’s tests, are recommended to analyze differences between two groups, and ANOVA-based methods, such as one-way ANOVA, two-way ANOVA, factorial ANOVA and MANOVA are used to evaluate more than two groups. Alternative univariate methods are implemented when the assumption of the normal distribution is non-parametric, such as Mann-Whitney test (MW-test) [51,81,102] and Wilcoxon test (W-test) [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differentiation is based on variance between groups by rejection of the null hypothesis or acceptation the alternate hypothesis [101,107,108]. The most common methods used when the data is parametric are T-tests [31,47,48,50,53,57,59,62,68,70,71,73,74,76,77,78,79,84] and ANOVA [33,44,46,63,64,66,68,69,72,83] T-tests, such as Student and Welch’s tests, are recommended to analyze differences between two groups, and ANOVA-based methods, such as one-way ANOVA, two-way ANOVA, factorial ANOVA and MANOVA are used to evaluate more than two groups. Alternative univariate methods are implemented when the assumption of the normal distribution is non-parametric, such as Mann-Whitney test (MW-test) [51,81,102] and Wilcoxon test (W-test) [58].…”
Section: Discussionmentioning
confidence: 99%
“…Unsupervised methods are the preferential option for exploratory studies, where the modeling process is based only on the explanatory variables, without external intervention of user (Yi et al, 2016). The most commons are principal component analysis (PCA) [56,57,60,62,70,75,76,80,92,93] and hierarchical cluster analysis (HCA) [33,43,51,56,59,76] PCA provides the projection of dataset into low dimensional based on orthogonal transformation, converting the variables variability from a set of observations into score vectors and loadings, called principal components [100,109]. HCA methods are used to form subsets of samples at ordered levels based on variables similarities/dissimilarities (such as distances or correlations) and can be performed in agglomerative mode (samples are aggregate into clusters) or divisive mode (complete dataset is divided into clusters).…”
Section: Discussionmentioning
confidence: 99%
“…Namely, glycerophosphocholines are overexpressed in BC compared to luminal and HER2 subtypes. In addition, Cho et al [5] have found differences in the content of triacylglycerols (TGs) in healthy and BC tissues, as well as certain changes in the PC profile of the BC lipid extracts using MALDI MS. Kim et al [17] developed an analytical approach for the determination of ketone-containing metabolites in human BC cell lines (e.g., MCF-7 cell line) as they can reflect the clinical condition and pathogenic mechanisms. Another report by Phillips et al [18] demonstrated that MALDI MS imaging (MALDI MSI) of peptides obtained from BC tissues of patients with triple-negative BC (TNBC) were useful to discover proteins with higher abundance in TNBC when compared with noncancerous tissue and use them in disease prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the identification of further matrix formulations, sample enrichment, improved sensitivity and mass range capabilities, a range of biological analytes can be accurately detected and analysed. The type of analytes routinely studied includes lipids [28], carbohydrates [29], nucleotides [30], metabolites [31] and hormones [32].…”
Section: Sample and Type Of Analytesmentioning
confidence: 99%